2021
DOI: 10.4322/acr.2021.328
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma presenting as acute tubulointerstitial nephritis

Abstract: Background: Acute tubulointerstitial nephritis (ATIN) is a very rare paraneoplastic manifestation in patients with multiple myeloma (MM). It is an uncommon pattern of renal disease in such patients. Case presentation: We report a case of an 82-year-old male who was admitted with acute kidney injury. Renal biopsy showed typical findings of light chainassociated ATIN with scattered inflammatory cells in the interstitium and associated active tubulitis. No other common manifestations of MM were present at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Despite this, it is well-known that more than 60% of patients with classical myeloma have BJP in their urine [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, it is well-known that more than 60% of patients with classical myeloma have BJP in their urine [27].…”
Section: Discussionmentioning
confidence: 99%
“…They are considered cornerstones with specific diagnostic importance in the context of target organ manifestations such as kidney failure, lytic bone lesions, anemia, or large numbers of plasma cells in the bone marrow of patients [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The International Kidney and Myeloma group does not categorize LCTIN as an entity expression of a plasma cell dyscrasia [7,8]; despite the growing interest and ongoing debate on the prognostic and therapeutic implications, literature is lacking [2,3,9,10]. From the literature review, we found that data on the prevalence of LCTIN are limited to only two series [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, the interstitial in ammation is an aspeci c nding since it is frequently reported in kidney biopsies as an expression of direct (e.g., nitric oxide production in the interstitium) or indirect (e.g., cytopathic damage against the tubular cells) insult of the kidney structures by the monoclonal light chains, according to their chemical and physical properties. However, in some patients, kidney biopsies show an inappropriately orid interstitial in ltration of in ammatory cells that may resemble allergic tubulointerstitial nephritis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In target organ manifestations of multiple myeloma like kidney failure, lytic bone lesions, anemia, or high numbers of plasma cells in the bone marrow of patients, Bence Jones proteins are critical diagnostic markers. In two thirds of cases of multiple myeloma, Bence Jones proteins are present [9,10].…”
Section: Introductionmentioning
confidence: 99%